2018
DOI: 10.3390/nu10121840
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Dense Diets and Mineral Metabolism in the Context of Chronic Kidney Disease–Metabolic Bone Disease (CKD-MBD)

Abstract: The aim of this paper is to review current knowledge about the interactions of energy-dense diets and mineral metabolism in the context of chronic kidney disease–metabolic bone disease (CKD-MBD). Energy dense-diets promote obesity and type II diabetes, two well-known causes of CKD. Conversely, these diets may help to prevent weight loss, which is associated with increased mortality in advanced CKD patients. Recent evidence indicates that, in addition to its nephrotoxic potential, energy-dense food promotes cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Some studies have suggested the existence of a relationship between obesity, energy-dense diets, and mineral metabolism in CKD [ 122 ]. According to them, energy-dense food generally tends to contain low levels of Ca and also to decrease its intestinal absorption as a result of the interaction between Ca and lipids in the intestinal lumen and subsequent formation of Ca soaps [ 123 , 124 ].…”
Section: Dietsmentioning
confidence: 99%
“…Some studies have suggested the existence of a relationship between obesity, energy-dense diets, and mineral metabolism in CKD [ 122 ]. According to them, energy-dense food generally tends to contain low levels of Ca and also to decrease its intestinal absorption as a result of the interaction between Ca and lipids in the intestinal lumen and subsequent formation of Ca soaps [ 123 , 124 ].…”
Section: Dietsmentioning
confidence: 99%
“…High-calorie diet in CKD patients, despite causing weight gain, is associated with less urea generation. In addition, weight loss and malnutrition correlated with worsened outcomes in CKD patients [ 28 ]. However, high-fat diets can reduce calcium absorption and consequently elevate 1,25(OH) 2 D, PTH, and phosphate absorption in CKD patients [ 28 ] and experimental animals [ 29 ].…”
Section: Nonpharmacological Approachmentioning
confidence: 99%
“…patients, promotes VC through several mechanisms, including increased serum CaxP product, and phenotypic transdifferentiation of vascular smooth muscle cells to osteochondrogenic cells [119]. Obesity and the caloric content of the diet influence uremic VC [78,120]. In experimental models of uraemia, obese Zucker rats have been shown to develop more severe VC than lean Zucker rats.…”
Section: Caloric Intake and Vcmentioning
confidence: 99%
“…Obesity and the caloric content of the diet influence uremic VC [ 78 , 120 ]. In experimental models of uraemia, obese Zucker rats have been shown to develop more severe VC than lean Zucker rats.…”
Section: Caloric Intake and Vcmentioning
confidence: 99%